Financial reporting of grants and assistance in self-financing units according IAS 20 - محمد صفاء احمد; حسن ريم سعدي (Journal of Economics and Administrative Sciences, 2017)
The objective of the research is to clarify the grants and aids as a conceptual input, identify the factors of obtaining them and their objectives, and the statement of the need to produce accounting information that enhances financial reporting related to grants and assistance, especially the presentation of the accounting treatments provided by the unified accounting system and determining the shortcomings of that system, The accounting requirements of IAS20 to limit the variation of treatments with application to the economic unit (the research sample) are presented. The study reached a set of conclusions, the most important of which is the absence of an accounting base in Iraq that determines the basis for accounting for grants and assistance upon receipt and after receipt, which makes it difficult to determine the basis of measurement and disclosure in the economic units as well as the existence of a difference between the accounting treatments provided by the accounting standards and what is stated in the consolidated accounting system The accounting standards address the types of grants and assistance as well as the preparation of financial statements explaining the course of use and the extent to which the requirements are met, while the unified accounting system lacks this, which adversely affects the accounting information provided. The study reached several recommendations, the most important of which is to propose an accounting rule for the treatment of grants and assistance adopting a method of measurement and accounting disclosure that can be applied by all economic units.